(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article explores the historical evolution, current status, and challenges of women’s rights in the context of the law. It highlights the transformation of legal systems from patriarchal structures to modern frameworks that aim to ensure gender equality and justice. The research focuses on the legal, social, and institutional barriers that have limited women’s access to justice and equal opportunities, as well as the progress achieved through international conventions and national reforms. Emphasis is placed on the role of law in empowering women, protecting their rights in family, labor, and political spheres, and addressing issues such as domestic violence, discrimination, and legal representation. The study underscores the importance of strengthening gender-sensitive legal mechanisms to promote fair and inclusive societies.